2022
DOI: 10.7759/cureus.25384
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Sex Hormones in Oral Squamous Cell Carcinoma: A Systematic Review on Immunohistochemical Studies

Abstract: Oral squamous cell carcinoma (OSCC) is the most widespread oral malignancy. In the western world, smoking and alcohol remain the most common risk factors, whereas smokeless tobacco and areca nut consumption are the prevalent etiological factors in South Asia. Numerous markers were studied till date to identify the disease. However, the role of sex hormones in OSCC is poorly defined. Hormonal receptors play a role in breast cancer, prostate cancer, and human papillomavirus (HPV) driven oropharyngeal cancers. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…For the clinical application, the production rate of Compounds A and B per month (at present, 50~60 mg each) should be scaled up. The present study suggests that Compounds A and B may destroy oral cancer cells that express estrogen receptors [ 37 , 38 ] without affecting normal cells in the oral cavity and the nervous system. Potential inhibition of estrogen-related receptor signaling pathways opens up possibilities for further research and application of these compounds in the field of hormone-dependent cancer and other diseases.…”
Section: Discussionmentioning
confidence: 86%
“…For the clinical application, the production rate of Compounds A and B per month (at present, 50~60 mg each) should be scaled up. The present study suggests that Compounds A and B may destroy oral cancer cells that express estrogen receptors [ 37 , 38 ] without affecting normal cells in the oral cavity and the nervous system. Potential inhibition of estrogen-related receptor signaling pathways opens up possibilities for further research and application of these compounds in the field of hormone-dependent cancer and other diseases.…”
Section: Discussionmentioning
confidence: 86%
“…To further confirm such an association among the estrobolome and cancer, some studies have found that the estrobolome has a different composition in people with or without oral cancer; in fact, people with oral cancer showed a higher presence of estrobolome bacteria (Saranya et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, tumors associated with high estrogen levels are characterized by marked hormonal signaling through the estrogens receptor (ER) interactions; as such, these pathways drive unreasonably high cellular proliferation. This increased cell growth coincides with enhanced mutation rates, due to metabolic activation facilitated by cytochrome P450 enzymes, ultimately leading to both genotoxic damage and the induction of aneuploidy (Saranya et al 2022).…”
Section: Introductionmentioning
confidence: 99%